Utilizing Artificial Intelligence to Enhance Employee Experience and Improve Human Resource Management Efficiency: A Performance Analysis of Companies - Wishah , Raed.H.; Zakzouk , Fida; Rawashdeh , Leila; Ahmed , Emad (Journal of Ecohumanism, 2025)
Purpose: This research aimed to assess the impact of AI in businesses that have implemented the technology to enhance employee satisfaction and optimize HRM efficiency. Design methodology approach: This study adopted a cross-sectional descriptive research design whereby the respondents’ data was collected at a single point in time. Participants included 180 international HR professionals working in organizations that have entities in the US, the UAE, and Jordan. Finding: Realize the potential benefits of AI for HRM, it is recommended that companies invest in such knowledge and expertise related to the field, integrate these solutions with other existing frameworks and systems without disrupting the process, prioritize data privacy and security, manage changes that the applications might bring to the employees, and seek affordable AI options that are specific to the needs of the human resource department. Practical implications: Enhanced efficiency and satisfaction, need for strategic investment in AI, data privacy and security considerations and cost-effectiveness and tailored solutions Originality/value: Providing empirical evidence on the impact of AI in HRM across different international contexts, specifically in the US, the UAE, and Jordan. The originality lies in the cross-sectional descriptive design which offers a snapshot of the current state of AI adoption in HRM and its effect and efficiency and employee satisfaction, furthermore, this research is particularly valuable for HR professionals, business leaders, and policymakers seeking to understand the nuances of AI integration in HRM and its implications for the future workforce.